Sex differences in competitive state anxiety of collegiate student-athletes in a state university college - Ruado, Mary Mhel 1999-
This study was conducted to measure and compare the 3 subscales of competitive state anxiety of male and female collegiate student-athletes at a state university 1-day before the college-level sports competition and 3-hours before the actual competition. The main objective of this study was to measure the competitive anxiety of male and female athletes in terms of psychological (cognitive), physiological (somatic), and behavioral (confidence). The population of this study was composed of student-athletes from different collegiate varsity teams competing in the second semester. The research was conducted using the Competitive State Anxiety Inventory- 2 questionnaires. A paired t-test was used to measure differences in cognitive, somatic, and self-confidence levels of male and female athletes 24 hours and 3 hours before the college-level sports competition. The independent t-test was used to measure and compare variances between males and females 1 day and 3 hours before the college-level sports competition. Paired t-test revealed that there is no significant difference in the 3 subscales of CSAI-2 in male athletes 24 hours and 3 hours before the competition while female athletes show a significant difference in somatic anxiety only. The independent t-test revealed that 24 hours before the competition between male and female athletes only cognitive anxiety and self-confidence level shows significant differences. 3 hours before the competition only self-confidence showed a significant difference